(untitled) (Eurasian Journal of Engineering and Technology, 2023)
The purpose.Creating ecologically and economically efficient biogas production technology by using high-water plant eichhornia and amaranth silage instead of animal and poultry manure, corn silage, which are considered scarce and expensive.